Perioperative coronary artery spasm leading to myocardial ischaemia after vein graft surgery. Issue 3 (March 1983) - Zingone, B; Salvi, A; Branchini, B
Abstract : Coronary artery spasm has been recognised recently as a possible cause of perioperative myocardial ischaemia after coronary artery bypass grafting. We report on one case and review the published reports. We emphasise the clinical picture of the patient who is liable to have spasm and the necessity for a prompt diagnosis and correct treatment.